Molecular neuroendocrinology : from genome to physiology - Murphy, David, 1957-; Gainer, Harold (Masterclass in neuroendocrinology series, 2016)
"Discusses the mechanisms that enhance peptide and protein diversity beyond what is encoded in the genome through post-translational modification"--